GEOGRAPHICAL FACTORS AFFECTING THE PRECIPITATION REGIME IN IRAN - SABZIPARVAR A.A.; MOVAHEDI S.; ASAKEREH H.; MASOODIYAN A.; MARYANAJI Z. (Aerul şi Apa: Componente ale Mediului, 2015)
This study compares the precipitation regime by using harmonic analysis during the last four decades (1965-2004).We used interpolated precipitation data from different weather stations distributed across Iran by applying 15x15 km spatial grids for the interpolated data. Data validations were employed by statistical tests. In this study three harmonies of precipitation variances were evaluated. Variability of precipitation regime was explored by using three-harmonic analysis method. In addition, the effect of geographical factors (altitude, latitude, longitude) affecting to the precipitation regime was verified. Analysis of the first harmonic method proved that the main precipitation regime in Iran occurs in winter season as result of large scale Mediterranean systems passing over Iran in the mentioned season. Moreover, the fluctuations of the seasonal precipitation regime were found to be different, so that in one region led to the appearance of the new regimes and in other region caused change or disappearance of the regimes. In all three harmonics, variances of precipitation were mainly a function of the geographical factors. This effect was more evident in the third harmonic, in such a way that the increases in latitudes (moving to northern region) caused higher precipitation variance. This means that precipitation regime in northern sites are more exposed to local factors and seasonal precipitation than those of southern sites. The results of this research can be used in land–use projects, environmental plans and water resources management.